Managing voluntary collective turnover: the impact of a cynical workplace climate - Brown, Michelle; Cregan, Christina; Kulik, Carol T.; Metz, Isabel (Personnel review, 2022)
PurposeVoluntary collective turnover can be costly for workplaces. The authors investigate the effectiveness of high-performance work system (HPWS) intensity as a tool to manage voluntary collective turnover. Further, the authors investigate a cynical workplace climate (CWC) as a boundary condition on the HPWS intensity–voluntary collective turnover relationship.Design/methodology/approachThe unit of analysis is the workplace, with human resource (HR) managers providing data on HPWS practices in Time 1 (T1) and voluntary collective turnover two years later. Aggregated employee data were used to assess the cynical workplace climate. Hierarchical regression analysis was used to test the hypotheses.FindingsThis study’s results demonstrate a negative relationship between HPWS intensity and voluntary collective turnover when there is a low cynical workplace climate. The authors find that in a high cynical workplace climate, HPWS intensity is ineffective at managing voluntary collective turnover.Research limitations/implicationsThis study’s results show that HPWS intensity needs to be well received by the workforce to be effective in reducing voluntary collective turnover.Practical implicationsTo increase the chances of HPWS intensity reducing voluntary collective turnover, workplaces need to assess the level of employee cynicism in their workplace climates. When the climate is assessed as low in cynicism, the workplace can then consider implementing an HPWS.Originality/valueThe authors explain why the HPWS intensity–voluntary collective turnover relationship varies across workplaces. As HR practices are subject to interpretation, workplaces need to look beyond the practices in their HPWS and focus on employee receptivity to HR practices.